Rethinking the Multidimensionality of Growth Mindset Amid the COVID-19 Pandemic: A Systematic Review and Framework Proposal - Ku, Yun-Ruei; Stager, Catanya (Frontiers in Psychology, 2022)
Students, staff, and faculty in higher education are facing unprecedented challenges due to the COVID-19 pandemic. A recent data collected by Statistics Canada measured the impacts of COVID-19 on postsecondary students and revealed that a good amount of academic activities and opportunities were disrupted as a result of the pandemic. While much uncertainty remains for the next academic year, how might higher education institutions and their students better respond to the rapidly changing situation matters. This commentary reviews a portion of growth mindset research and advocates the importance of being resilient in the face of the pandemic. Although growth mindset has been identified as a sole concept, it is actually comprised of multiple sub-abilities such as self-control, emotion regulation, and cognitive reappraisal which will lead us to the ultimate goal. Therefore, educators in higher education must rethink the multidimensionality of growth mindset and help their students recognize alternative routes to their objectives set before the pandemic. Although the campuses had been shut down, these challenges have brought students unique opportunities to boost their psychological and physical well-beings.